2019
DOI: 10.26418/positron.v9i2.35072
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Karakteristik Kekeringan DAS Kapuas Kalimantan Barat Berdasarkan Luaran Global Climate Model

Abstract: AbstrakDaerah aliran sungai (DAS) Kapuas, walaupun berada di wilayah benua maritim Indonesia dengan curah hujan yang tinggi sepanjang tahun, namun sering mengalami kebakaran lahan dan hutan. Bencana kebakaran lahan dan hutan tersebut merupakan dampak dari kekeringan yang berkepanjangan. Informasi tentang karakteristik kekeringan di wilayah DAS Kapuas masih kurang diungkap terutama terkait dengan penggunaan data iklim global. Penelitian ini bertujuan untuk menganalisis karakteristik kekeringan meteorologis dan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
2
0
2
Order By: Relevance
“…The findings of the SPI and SRI drought index assessments have been separated in research conducted in Indonesia. Research result [45] performed in the Kapuas watershed revealed that while there were variations in the results for the frequency and length of drought episodes, both revealed that these variables varied and had a tendency to rise in tandem with El-Nio occurrences.…”
Section: Selection Of Drought Index Methods For Drought Characteristi...mentioning
confidence: 97%
See 1 more Smart Citation
“…The findings of the SPI and SRI drought index assessments have been separated in research conducted in Indonesia. Research result [45] performed in the Kapuas watershed revealed that while there were variations in the results for the frequency and length of drought episodes, both revealed that these variables varied and had a tendency to rise in tandem with El-Nio occurrences.…”
Section: Selection Of Drought Index Methods For Drought Characteristi...mentioning
confidence: 97%
“…This division is used to find out the drought index data of the past (history), present, and future [42,50]. The division is also made based on the needs of the researcher, such as the distribution of the analysis of 10 years, 20 years or 50 years in 1 time span [25,31,45]. The selection of the time span is due to several considerations, including paying attention to historical periods for assessing future periods [36,42], considered to represent the climatological rainfall of each station [35], and data availability [31].…”
Section: Research Area and Research Time Rangementioning
confidence: 99%
“…Kekeringan dapat diklasifikasikan berdasarkan karakteristik dan dampak yang ditimbulkan [7]. Bencana kekeringan merupakan ancaman serius secara global dan diproyeksikan akan semakin parah di masa mendatang [8]. Terdapat empat tipe kekeringan yaitu: (1) Kekeringan meteorologi adalah kekeringan yang terjadi ketika suhu tinggi dan curah hujan yang rendah menyebabkan kekeringan di suatu wilayah.…”
Section: Pendahuluanunclassified
“…Fenomena El-Niño merupakan kejadian global yang menyebabkan penurunan curah hujan di wilayah Indonesia dan berdampak peningkatan kekeringan (Taufik et al, 2017;Ihwan et al, 2019). Peristiwa kebakaran hutan dan lahan dalam skala besar pernah terjadi di Indonesia pada tahun 2015 khususnya di Pulau Sumatra, Kalimantan dan Papua, dengan luas hutan dan lahan yang terbakar di Indonesia sebesar 2.611.411,44 ha, sebanyak 3,6% terjadi di Kalimantan Barat (SiPongi, 2023).…”
Section: Pendahuluanunclassified